Proses Penerbitan Grosse Akta Kapal di KSOP Khusus Batam pada PT. Gardatama Anugerah Segara Sejahtera Batam - Jusdi Simarmata; Fadiyah Hani Sabila (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This paper aims to find out the process of issuance of grosse deed of vessel at KSOP Khusus Batam and to find out the document requirements attached to the issuance of grosse deed of vessel. The methods used in this research are field research and library research. The process of issuance of ship deed grosse at KSOP Khusus Batam is conducted through procedures and requirements that have been set. It aims to ensure the validity and legality of ship ownership in accordance with the provisions of the prevailing laws and regulations. The results of the research in the discussion of the problem of the process of issuing the ship's deed grosse are regulated in PM No. 39 of 2017 concerning Registration and Nationality of Ships authorised by the Minister of Transportation. The process of issuing Grosse Deed of Ship at KSOP Khusus Batam at PT Gardatama Anugerah Segara Sejahtera Batam has been done well but there are still obstacles, namely the error in uploading attachment documents on the ship registration application system so that it causes the submission to be revised, as well as in bringing and checking the physical requirement documents at the time of physical file validation at KSOP Khusus Batam.